Comparação de guias cirúrgicas para osteotomia periacetabular quanto à eficiência mecânica através de simulação por elementos finitos - dos Santos Rodrigues, Ewerson (2024)
Guides are tools created to assist in the precision of surgical procedures. In the case of periacetabular osteotomy, the guides are generated from medical images obtained by computed tomography in order to fit perfectly to the patient’s pelvic bone. Slots are created in the guides for the proper insertion of chisels that perform the osteotomy and are ultimately constructed through the additive manufacturing process (3D printing). Since the surgical site is difficult to access and of restricted size, it is beneficial for the guides to be perforated to enhance local visibility, and they should also have dimensions compatible with this area to avoid compromising the surgical procedure. However, due to the impact of the chisels, forces may be transmitted to the guides, necessitating them to be mechanically resistant. Through the finite element method, different guides are tested to assess their mechanical efficiency, using mesh editing programs to generate distinct patterns. Due to the difficulties in converting medical images into geometric models, some protocols are tested to minimize artifacts that hinder the importation of models into analysis programs. Mesh cleaning, correction, and smoothing techniques are employed, and to expedite the task, a Python code is developed to automate their generation based on predefined parameters.